A Geochemical Characterization of a Cold-Water Acid Rock Drainage Stream Emanating From the Zn-Pb XY-deposit, Howard's Pass, Yukon Territory, Canada - Feige, Kristen B. (Université d'Ottawa / University of Ottawa, 2011)
An acid rock drainage (ARD) stream emanating from the Zn-Pb XY-deposit in the Yukon Territory was examined in order to evaluate the physico-chemical and geochemical processes governing the distribution of dissolved elements from the creek. The creek showed very high concentrations of metals (300 mg/L Fe, 500 mg/L Zn, 15 000 µg/L Ni, 1300 µg/L Cu and 4500 µg/L Cd), low water temperatures (1 – 12°C) and was acidic to moderately acidic (pH 3.1 – 5.0). It was found that this stream experienced a strong seasonal evolution, with increased sulphate and metal concentrations and decreased pH over the course of the summer. The mineral precipitates that formed under low pH conditions were a mixture of schwertmannite, goethite, jarosite and barite, while those that formed under moderately acidic conditions were a mixture of jurbanite, hydrobasaluminite, gibbsite and an X-ray amorphous Al-sulphate phase. Most of the mineral precipitates were of inorganic origin, although microbes may have played a role in mineral formation and trace metal sequestration in some of the precipitates. All of the mineral precipitates contained anomalous concentrations of trace elements (up to 1.5 % wt Zn) and showed a seasonal evolution in their mineralogy, both of which were determined to be a function of the pH and prevailing geochemical conditions. The geochemistry of the ARD creek draining the XY-deposit was compared to another ARD creek in the area that was likely draining shales. The two creeks were compared in order to determine if ARD geochemical characteristics can be used as a tool for the mineral exploration industry.
Keywords: Acid rock drainage; Zn-Pb SEDEX; Yukon Territory; geochemistry; Howard's Pass